Environmental management and sustainability : a study on the precautionary principle focusing on health and food hygiene safety - Razman, Muhammad Rizal; Supian, Suffeiya; Ramli, Nor Azam; Azlan, Azrina; Che Ngah, Mohamad Suhaily Yusri (WFL Publisher, 2013)
The use of the precautionary principle to the area of environmental management and sustainability is largely in response to the necessity of each individual state to protect rights and interests in order to safeguard the Mother Nature. Therefore, this study examines the use of the precautionary principle in the Malaysian food hygiene regulations in relation to the environmental management and sustainability from the legal perspectives; identify actions, which deal with the protection of the environment as well as a tool for the achievement of sustainable development.